1962
DOI: 10.1063/1.1724264
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of a Classical Gravitational Field Interacting with Quantized Matter Fields

Abstract: The behavior of the mean value of the energy-momentum tensor of a set of quantized matter fields interacting with a classical gravitational field which is, in turn, produced by this mean value, is investigated. Singularities appear in the energy-momentum tensor corresponding to divergences of three different orders: ∞4, ∞2, and log ∞. These can be removed by the introduction of counter terms into Einstein's equation. The ∞4 singularity is removed by a ``cosmological term,'' the ∞2 singularity by a renormalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
506
0
3

Year Published

1963
1963
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(517 citation statements)
references
References 1 publication
8
506
0
3
Order By: Relevance
“…These divergences are similar to those described in [32]. To characterize them, one plugs in (41)-(42) the adiabatic expansion of h I k and h II k , given in Eq.…”
Section: Renormalization Of the Stress-energy Tensor T µν And Thementioning
confidence: 94%
“…These divergences are similar to those described in [32]. To characterize them, one plugs in (41)-(42) the adiabatic expansion of h I k and h II k , given in Eq.…”
Section: Renormalization Of the Stress-energy Tensor T µν And Thementioning
confidence: 94%
“…The predicted magnitudes of these effects are obtained through renormalization of fields and coupling constants, which absorb the infinities in a covariant manner. Renormalization methods have long been extended to quantized fields propagating in the curved spacetime of general relativity [6] (see also [7] and references therein), but predicted quantum vacuum effects of curved spacetime have been too small to be directly observed. Quantum vacuum effects in curved spacetimes have also been explored in connection with particle creation by the expansion of the universe and by black holes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The first two terms have been calculated explicitly as χ 1 = 1/2 and χ 2 = 3/4 [37,12]. 2 We have then shown that these are universal values independent of the gauge group and the contents of matter fields as far as they are conformally coupled. 3 The bare quantity t 0 is a single dimensionless gravitational coupling constant, while b 0 is not an independent coupling as mentioned below.…”
Section: Quantum Gravity Actionmentioning
confidence: 99%
“…The quantization of gravity based on the Einstein action [2,3,4] has a lot of difficulties. First of all, the theory is not renormalizable.…”
Section: Introductionmentioning
confidence: 99%